A M35 family metalloprotease is required for fungal virulence against insects by inactivating host prophenoloxidases and beyond - Huang, Antian (Virulence, 2020)
A diverse family of metalloproteases (MPs) is distributed in eukaryotes. However, the functions of MPs are still understudied. We report that seven MPs belonging to the M35 family are encoded in the genome of the insect pathogenic fungus Metarhizium robertsii. By gene deletions and insect bioassays, we found that one of the M35-family MPs, i.e. MrM35-4, is required for fungal virulence against insect hosts. MrM35-4 is a secretable enzyme and shows a proteolytic activity implicated in facilitating fungal penetration of insect cuticles. After gene rescue and overexpression, insect bioassays indicated that MrM35-4 contributes to inhibiting insect cuticular and hemocyte melanization activities. Enzymatic cleavage assays revealed that the recombinant prophenoloxidases PPO1 and PPO2 of Drosophila melanogaster could be clipped by MrM35-4 in a manner differing from a serine protease that can activate PPO activities. In addition, it was found that MrM35-4 is involved in suppressing antifungal gene expression in insects. Consistent with the evident apoptogenic effect of MrM35-4 on host cells, we found that the PPO mutant flies differentially succumbed to the infections of the wild-type and mutant strains of M. robertsii. Thus, MrM35-4 plays a multifaceted role beyond targeting PPOs during fungus-insect interactions, which represents a previously unsuspected strategy employed by Metarhizium to outmaneuver insect immune defenses.